Behavior of the bison and helminthoses (European Bison Conservation Newsletter, 2010)
The purpose of this paper is to present some relations between European bison behavior and possibility of parasite infection based on observation done in the European Bison Breeding Centre of the Prioksko-Terrasnyjj State Natural Biosphere Reserve. The knowledge of animals habits and their daily schedule is very important for applying proper anti-parasitic program. In captive conditions it is also is necessary to estimate the epizootic situation of parasitic illnesses, a prediction of their tendency in time and elaborate the modern system of parasitic prevention.
Keywords: European bison; anti-parasite treatment; captive condition